Effect of lithium addition on Te4+ emission in TeO2-Li2O glasses - Costa, Francine Bettio [UNESP]; Souza, Ana Kely Rufino; Silva, Junior Reis; Moraes, João Carlos Silos [UNESP]; de Oliveira Nunes, Luiz Antonio; da Cunha Andrade, Luis Humberto; El-Mallawany, Raouf; Lima, Sandro Marcio (Elsevier, 2019)
Lithium tellurite glasses with xTeO2 + (100 − x)Li2O nominal composition, where x = 95, 90, 85, 80, 75 and 70 mol%, have been prepared to investigate the dependence of the Te4+ emission as a function of the lithium modifier. Optical and structural properties of the glasses were explored by using UV–Vis absorption, photoluminescence and photoluminescence excitation spectroscopies, photoluminescence lifetime and Raman spectroscopy. Besides, the influence of Li2O in the glass structure was verified by density, glass transition temperature, thermal stability, glass-forming tendency, optical band edge and the number of non-bridging oxygen. The results support there is a good correlation between the glass structure and the Te4+ center concentration: the Li2O content contributes to increase the Te4+ in the glass structure.
Keywords: Lithium as modifier; Photoluminescence; Te4+ centers; Tellurite glasses